Pemanfaatan Autotransformator Sebagai Pengontrol Arus Start Motor Induksi Tipe LH 73204 Guna Menjaga Kesetabilan Tegangan Listrik di Laboratorium Konversi Energi Teknik Elektro Universitas Udayana - -, I Wayan Lastera (Majalah Ilmiah Teknologi Elektro; Vol 18 No 2 (2019): (Mei-Agustus) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2019.v18i02.P09, 2019)
Practicum activities at the Energy Conversion Laboratory of Electrical Engineering Udayana University, using induction motors that operated directly connected to the power source, so that start current of the motor becomes large enough to cause electrical voltage stability to be disturbe. Conditions like these can damage other laboratory equipment. So that research using autotrasformator as a starting, the aims to produce a model of controlling the starting current on the operation of induction motor Type LH73204. In research, the input voltage to the motor is gradually lowered from 220 Volts to 88 Volts with autotransformator at the start of the motor, then motor starting current is observed for each phase of the input voltage drop. Data were tabulated and analyzed descriptively, showed that the utilization autotransformator starting current operation induction motor type LH 73204 capable suppressed 44,11% or 3 Apere lower. so that becomes a model and test method for controlling the starting current induction motor. This model is very useful for maintaining electrical voltage stability, so that laboratory equipment works optimally.